Selection of target mutation in rat gastrointestinal tract E. coli by minute dosage of enrofloxacin - Lin, Dachuan; Chen, Kaichao; Li, Ruichao; Liu, Lizhang; Guo, Jiubiao; Yao, Wen; Chen, Sheng (Frontiers in Microbiology, 2014)
It has been suggested that bacterial resistance is selected within a mutation selection window of antibiotics. More recent studies showed that even extremely low concentration of antibiotic could select resistant bacteria in vitro. Yet little is known about the exact antibiotic concentration range that can effectively select for resistant organisms in animal gastrointestinal (GI) tract. In this study, the effect of different concentrations of enrofloxacin on resistance and mutation development in rat GI tract E. coli was investigated by determining the number of resistant E. coli recoverable from rat fecal samples. Our data showed that high dose antibiotic treatment could effectively eliminate E. coli with single gyrA mutation in the early course of treatment, yet the eradication effects diminished upon prolonged treatment. Therapeutic and sub-therapeutic dose (1/10 and 1/100 of therapeutic doses) of enrofloxacin could effectively select for mutation in GI tract E. coli at the later course of enrofloxacin treatment and during the cessation periods. Surprisingly, very low dose of enrofloxacin (1/1000 therapeutic dose) could also select for mutation in GI tract E. coli at the later course of enrofloxacin treatment, only with slightly lower efficiency. No enrofloxacin-resistant E. coli could be selected at all test levels of enrofloxacin during long term treatment and the strength of antibiotic treatment does not alter the overall level of E. coli in rat GI tract. This study demonstrated the response of rat GI tract E. coli to different concentrations of enrofloxacin treatment and provided insight into the rational use of antibiotics in animal husbandry.